Metastatic calcification and nephrosclerosis in an adult sloth (Choloepus hoffmani) - Olivares, Roberto W. I.; Brautigäm, Andrés Saenz (Brazilian Journal of Veterinary Pathology, 2022)
Multiple fragments of various organs from the necropsy of an adult sloth (Choloepus hoffmani) were received. The animal, prior to its death, had presented decay and poor general body condition, which is why it was euthanized.